2014
DOI: 10.1083/jcb.201304101
|View full text |Cite
|
Sign up to set email alerts
|

BARP suppresses voltage-gated calcium channel activity and Ca2+-evoked exocytosis

Abstract: The integral membrane glycoprotein BARP associates with voltage-gated calcium channel Cavβ subunits, disrupting their association with Cavα1 subunits and suppressing overall channel activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 76 publications
(109 reference statements)
2
20
0
Order By: Relevance
“…Our screen identified BARP and inositolrequiring enzyme-1α (IRE1α) as α6β4 enhancers. BARP is a single-pass transmembrane protein that was first identified in association with voltage-gated calcium channel β subunits (14) and was later found as an accessory component of α6β2β3 nAChRs (13), while IRE1α is a constituent of the unfolded protein response (UPR) (15). We found that the efficacy of nicotinic agonists to treat neuropathic pain best correlates with their activity on α6β4 receptors.…”
Section: Introductionmentioning
confidence: 92%
“…Our screen identified BARP and inositolrequiring enzyme-1α (IRE1α) as α6β4 enhancers. BARP is a single-pass transmembrane protein that was first identified in association with voltage-gated calcium channel β subunits (14) and was later found as an accessory component of α6β2β3 nAChRs (13), while IRE1α is a constituent of the unfolded protein response (UPR) (15). We found that the efficacy of nicotinic agonists to treat neuropathic pain best correlates with their activity on α6β4 receptors.…”
Section: Introductionmentioning
confidence: 92%
“…phosphorylation/ dephosphorylation, or after dissociation from a binding partner. A recent study suggests that BARP (β‐anchoring and ‐regulatory protein), a transmembrane protein expressed in the brain and in pancreas, could act as such a donor of β subunits (Beguin et al, ).…”
Section: Dynamic Subunit Composition Of Vgcc Complexesmentioning
confidence: 99%
“…This integral membrane glycoprotein is predominantly expressed in neurons and neuropeptide secretory cells. In fact, high BARP mRNA levels were located in brain, pancreatic islets and neuroendocrine cell lines (MIN6 and PC12), with no or weak expression in other tissues [88]. Interestingly, in the brain and cerebellum, BARP co-immunoprecipitated with Ca v β 3 and Ca v β 4 but not with Ca v β 1 suggesting that BARP may associate with specific Ca v β in particular sub-cellular domains of neurons.…”
Section: Barp Negatively Regulates Vgcc Activity Via Ca V βmentioning
confidence: 89%
“…Thus, BARP controls the localization of Ca v β and its association with Ca v α 1 to negatively regulate VGCC activity. These findings may lead to new strategies for the design of original therapeutic VGCC blockers [88].…”
Section: Barp Negatively Regulates Vgcc Activity Via Ca V βmentioning
confidence: 98%
See 1 more Smart Citation